Long-term metabolic and nutritional effects of laparoscopic sleeve gastrectomy and Roux-en-Y gastric bypass in the treatment of severe obesity - Saarinen, Ilmari (fi=Turun yliopisto|en=University of Turku|, 2025)
Background: Metabolic bariatric surgery (MBS) is the most effective treatment of severe obesity, a global epidemic associated with multiple comorbidities. MBS may result in type 2 diabetes (T2D) remission. The Individualized Metabolic Surgery (IMS) score aims to predict the remission and guide procedure selection between the two most common MBS procedures, laparoscopic sleeve gastrectomy (LSG) and Roux-en-Y gastric bypass (LRYGB). The Finnish SLEEVEPASS trial is a randomized multicenter clinical trial with long-term follow-up comparing LSG and LRYG. Severe obesity is associated with low-grade chronic inflammation, which is considered to contribute to the development of comorbidities and increased cancer risk. MBS may cause nutritional deficiencies, and micronutrient supplements are recommended postoperatively. Aims: The aim of this thesis was to evaluate and compare long-term metabolic and nutritional effects of LSG and LRYGB. Study I aimed to validate the IMS score. Study II assessed the effect of MBS on low-grade chronic inflammation using high-sensitivity C-reactive protein (hs-CRP). Study III evaluated long-term nutritional deficiencies and adherence to micronutrient supplements at 10 years. Results: IMS score correlated with the probability of T2D remissions, but there was no statistically significant difference between the procedures to guide procedure selection. MBS resulted in long-term decrease in hs-CRP, which correlated with BMI through follow-up. Long-term nutritional deficiencies were rare after MBS. There was a statistically significant difference between LSG and LRYGB in iron deficiency. Adherence to micronutrient supplements was higher in LRYGB group. Conclusions: IMS score demonstrated strong prediction of T2D remission, but did not facilitate procedure selection. Hs-CRP decreased sustainably after MBS with weight loss as the driving force. Nutritional deficiencies were relatively rare after MBS, except for iron deficiency, which should be monitored, especially after LRYGB and considered in procedure selection.

Tausta: Vaikea lihavuus liitännäissairauksineen on maailmanlaajuinen terveysongelma. Tehokkain hoito vaikeaan lihavuuteen on lihavuuskirurgia, jolla voidaan aikaansaada tyypin 2 diabeteksen (T2D) remissio. Individualized Metabolic Surgery (IMS) -pisteytys pyrkii ennustamaan T2D:n remission todennäköisyyttä ja ohjaamaan valintaa kahden yleisimmän lihavuuskirurgisen leikkausmenetelmän, laparoskooppisten mahalaukun kavennuksen (LSG) ja mahalaukun Roux-en-Y ohitusleikkauksen (LRYGB), välillä. Suomalainen SLEEVEPASS-tutkimus on pitkän aikavälin satunnaistettu kliininen monikeskustutkimus, jossa vertaillaan kavennusta ja ohitusleikkausta. Vaikea lihavuus aiheuttaa kehoon matala-asteisen tulehdustilan, jonka uskotaan vaikuttavan liitännäissairauksien kehittymiseen ja syöpäriskiin. Lihavuusleikkauksen jälkeen potilaat saattavat kärsiä ravintoainepuutoksista ja heille suositellaan pysyvää vitamiinilisien käyttöä. Tavoitteet: Tämä väitöskirja pyrkii arvioimaan ja vertailemaan LSG:n ja LRYGB:n pitkäaikaisvaikutuksia aineenvaihduntasairauksiin ja ravitsemukseen. Osatyön I tavoitteena oli validoida IMS-pisteytys. Osatyössä II tutkittiin leikka-uksien vaikutusta matala-asteiseen tulehdustilaan herkän C-reaktiivisen proteiinin (hs-CRP) avulla. Osatyö III arvioi ravintoainepuutosten yleisyyttä ja vitamiinilisien käyttöä 10 vuoden kohdalla leikkauksesta. Tulokset: IMS-pisteet olivat selvästi yhteydessä T2D:n remissioon, mutta menetelmien välillä ei ollut eroa. Hs-CRP laski leikkausten jälkeen korreloiden selvästi painonlaskun kanssa. Ravintoaineiden puutokset olivat harvinaisia pitkällä aikavälillä leikkausten jälkeen. Menetelmien välillä oli eroa vain raudanpuutteessa. Vitamiinilisien käyttö oli yleisempää LRYGB-ryhmässä. Johtopäätökset: IMS-pisteytys ennusti T2D:n remissiota, mutta ei helpottanut menetelmän valintaa. Hs-CRP laski leikkausten jälkeen pitkäaikaisesti painonlaskun myötä. Ravintoaineiden puutokset olivat harvinaisia leikkauksen jälkeen, lukuun ottamatta raudanpuutetta, jota tulisi seuloa etenkin LRYGB:n jälkeen ja huomioida menetelmän valinnassa.